Daphnane diterpenoids with nitric oxide inhibitory activities and interactions with iNOS from the leaves of Trigonostemon thyrsoideus. (March 2018) - Liu, Feng; Yang, Xueyuan; Liang, Yue; Dong, Bangjian; Su, Guochen; Tuerhong, Muhetaer; Jin, Da-Qing; Xu, Jing; Guo, Yuanqiang
Abstract: A phytochemical investigation to search for new nitric oxide (NO) inhibitors resulted in the isolation of seven previously undescribed daphnane diterpenoids, thyrsoidpenes A−G, from the leaves of Trigonostemon thyrsoideus . Their structures including absolute configurations were elucidated on the basis of extensive NMR spectroscopic data analysis and the time-dependent density functional theory (TDDFT) electronic circular dichroism (ECD) calculations. Thyrsoidpenes B−G feature rare polycyclic caged structures of daphnane diterpenoid orthoester. The NO inhibitory effects were examined and all of the compounds showed inhibitory activities toward LPS-induced NO production in murine microglial BV-2 cells. The possible mechanism of NO inhibition of some bioactive compounds was also investigated using molecular docking, which revealed the interactions of bioactive compounds with the iNOS protein. Graphical abstract: Seven previously undescribed daphnane diterpenoids, thyrsoidpenes A−G, were isolated and characterized from Trigonostemon thyrsoideus . All of the compounds showed inhibitory effects on NO production. Highlights: Seven previously undescribed diterpenoids were isolated from Trigonostemon thyrsoideus. The structures were elucidated by NMR data and ECD calculations. Thyrsoidpenes B− G possess caged structures of daphnane diterpenoid orthoester. All of the compounds showed NO inhibitory effects. Molecular docking revealed strong interactions between compounds and iNOS.